CULTURAL APPROACH TO REDUCED TRAFFIC ACCIDENT IN BALI - Sutjana, I.D.P. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 2, No. 1 Maret 2008)
Safety on traveling is needed by all travelers. Safety on traveling is determined bymany factors such as the drivers, vehicles, road, environment and it relation each other.Balinese culture which influence by Hinduism, believe that traffics accidents occurred asa result of not harmonize the relation between human as a driver to vehicle or car, humanto the god and human to the environment. So in Balinese daily of life there is an effort toharmonize the relation of all components using cultural approach. In doing that manyactivities such as doing an offering to the new or after reparation of car, to offer sajen inthe car everyday during traveler, every 210 days during “ tumpek landep day” aftercleaning the car offer sajen, ring the bell or offer sajen during passing the sacral place ortemple, offer sajen and look after during night where the accident were happen, offersajen (mlaspas) the new road, forbidden to travel during wedding ceremony or get familydied. These activities mean to making the tools more humane so that the tools harmonizeto the user, forgive to the magic spirit around the road. By practicing the culturalapproach the traffic accident at many places can be reduced. One taxi company shownthat annually maintenance cost lower compared than the same company in Java.
Keywords: Safety, cultural approach, accident